Pengembangan Media Pembelajaran Komik Digital Berbasis Flipbook Pada Muatan IPAS Untuk Meningkatkan Hasil Belajar Siswa - Alfi Riski Ramadanti; Kurniana Bektiningsih (Journal for Lesson and Learning Studies, 2023)
The problem that often occurs today in schools is the need for more learning media that supports learning activities, making learning boring. This research aims to develop flipbook-based digital comic learning media on science content to improve student learning outcomes. This type of research is development research using the Borg and Gall model. The subjects in this research consisted of 23 students of class IV B. The data collection techniques used were test and non-test techniques. Observations, questionnaires, and interviews carry out non-test techniques. Meanwhile, the test technique is carried out using pretest and posttest. Data collection instruments use questionnaires and test questions. The techniques used to analyze the data are qualitative, quantitative, and N-gain descriptive analysis. The research results, namely the results of expert tests carried out by material experts, obtained a percentage of 91.7% with very feasible criteria and 90% for media experts with very feasible criteria. Based on effectiveness, the learning outcomes of class IV students have increased on average from 55 to 85. It is proven by the N-Gain test, namely an N-Gain of 0.69, which shows the category is quite effective. It was concluded that flipbook-based digital comics in science and science learning, norm material in my local customs, were valid and suitable for learning. This research implies that using flipbook-based digital comics can improve student learning outcomes.